HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN KEJADIAN INSOMNIA PADA LANSIA DI UPT PSTW KHUSNUL KHOTIMAH PEKANBARU - Febrianita, Yulia (PROGRAM STUDI DIII KEPERAWATAN UNIVERSITAS ABDURRAB PEKANBARU, 2016)
Old age is an event that will surely be experienced by everyone who has a long age, the occurrence can not be avoided by anyone. In old age will occur in various organs setback. Old age, the mean phase of the life cycle that begins at age 65. Gerontology experts divide the elderly into two groups: older middle age aged 65-74 years, old age is old (old-old) age 75 years and older. This study aims to look at the relationship between anxiety levels with the incidence of insomnia in the elderly in the UPT PSTW Khusnul Khotimah Pekanbaru. This research is correlation. Samples taken using the technique of sampling the total sample amounted to 25 people. The meter used is a questionnaire. The analysis used was univariate and bivariate analysis, the test used is the Kolmogorov-Smirnov test. anxiety level is mild as many as 6 people (24.0%), and severe anxiety levels were 19 men (76.0%) . Of the dependent variable in getting the results the level of insomnia: the level of short-term insomnia 6 people (24%), while 12 people (48%), and chronic 7 people (28%). From the statistical tests using the Kolmogorov-Smirnov in get (P> 0.05) This means that the results showed no relationship between anxiety levels with the incidence of insomnia in the elderly. Based on the results of these studies are suggested for nurses to provide counseling or information to the elderly so as to minimize the occurrence of insomnia in the elderly.